EFFECTS OF SMALL-GROUP STUDENT TALK ON THAI UNDERGRADUATE STUDENTS’ INDIVIDUAL WRITING PERFORMANCE - Rachawong, Massaya (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This quasi-experimental study, included a pretest and a posttest, aimed to investigate the effects of small-group student talk on Thai undergraduate students’ individual writing performance. The participants of the study were 34 second-year English majored students at Loei Rajabhat University. They were randomly assigned to an experimental group and a control group to investigate whether employing small-group student talk would effectively facilitate students’ individual writing performance. The participants in the experimental group were divided into a small group of four for planning during a prewriting task, while the participants in the control group worked individually. The effects after the quasi-experimental study were measured by the analytic scores on five components of the writing task and the holistic writing scores cumulated of all these components. Statistical analyses revealed that the two groups were significantly distinguished by the analytic and holistic scores, indicating that participants in the experimental group performed better than peers in the control group. The effects of small-group student talk were found statistically significant in facilitating students’ writing improvement in all five aspects: content, organization, vocabulary, and language use, mechanics.